A Programmable Solution for Stepped Crane Columns - Moore, II (Engineering Journal, 1986)
The basic equations for the solution of a stepped column with a fixed base are easily derived, but the pinned top equations are the only forms found in generally available literature such as the AISC book on Industrial Buildings. This paper presents the 10 basic equations required for a general solution of the stepped crane column and describes the use of these equations with the generally accepted Murray-Graham model of crane column action. The 10 equations are applicable to both bayonet and double-shaft crane columns and by setting I equal to I may be applied to single-shaft columns with a bracketed crane girder. The equations also allow the designer to locate the crane thrust at the proper location instead of at the column step, a refinement which complicates needlessly the solution for manual calculation but which presents no problem to the computer.